Workplace violence in convenience stores - Pandee, Piyapat; Jiamjarasrangsi, Wiroj (Chulalongkorn Medical Journal, 2020)
Workplace violence is a problem that can occur in any occupation and at any operational level. Each occupation has different levels of risks depending on factors including personal factors (i.e. workers and service users), temporal factors, and location factors. Of all workplaces, convenience stores are considered one of the top places with frequent violence. Partially, this is because there are many factors different from other workplaces. Those factors may lead to violence and crimes such as verbal harassment, physical harms, robbery, and murder. The mentioned violence does not only have direct physical effects but also has short-term and long-term mental effects as well as economic and social effects. This article presents the extensive review of the violence at convenience stores. Its contents consist of the introduction, the definition of the workplace violence, the sizes of the violence at the convenient stores, the effects of workplace violence, the factors of the violence at the convenience stores, and relevant studies about convenience stores in Thailand, and conclusions.